1jikannsuu hatten04 1 5test

10 

Loading....

Loading....

Loading....

Loading....

Loading....

全文

(1)

(1) −3y+ 2x= 6

5

−5

5

−5

x y

O

(2) 3y2x= 15

5

−5

5

−5

x y

O

(3) −x+ 2y−2 = 0

5

−5

5

−5

x y

O

(4) 3x−4y=−24

5

−5

5

−5

x y

O

(5) −4y−3x= 8

5

−5

5

−5

x y

O

(6) x−2y=−10

5

−5

5

−5

x y

O

(7) −x+ 2y = 10

5

−5

5

−5

x y

O

(8) 4y+x20 = 0

5

−5

5

−5

x y

O

(9) x−3y=−9

5

−5

5

−5

x y

O

(2)

(1) −3y+ 2x= 6

5

−5

5

−5

x y

O

(2) 3y2x= 15

5

−5

5

−5

x y

O

(3) −x+ 2y−2 = 0

5

−5

5

−5

x y

O

(4) 3x−4y=−24

5

−5

5

−5

x y

O

(5) −4y−3x= 8

5

−5

5

−5

x y

O

(6) x−2y=−10

5

−5

5

−5

x y

O

(7) −x+ 2y = 10

5

−5

5

−5

x y

O

(8) 4y+x20 = 0

5

−5

5

−5

x y

O

(9) x−3y=−9

5

−5

5

−5

x y

O

(3)

(1) −3x−4y= 8

5

−5

5

−5

x y

O

(2) −3y−x+ 3 = 0

5

−5

5

−5

x y

O

(3) −4x+ 3y−6 = 0

5

−5

5

−5

x y

O

(4) 3x−4y=−16

5

−5

5

−5

x y

O

(5) 3y−2x−18 = 0

5

−5

5

−5

x y

O

(6) x−3y−9 = 0

5

−5

5

−5

x y

O

(7) 2y+ 3x=4

5

−5

5

−5

x y

O

(8) 2x+ 3y+ 6 = 0

5

−5

5

−5

x y

O

(9) −x−3y+ 6 = 0

5

−5

5

−5

x y

O

(4)

(1) −3x−4y= 8

5

−5

5

−5

x y

O

(2) −3y−x+ 3 = 0

5

−5

5

−5

x y

O

(3) −4x+ 3y−6 = 0

5

−5

5

−5

x y

O

(4) 3x−4y=−16

5

−5

5

−5

x y

O

(5) 3y−2x−18 = 0

5

−5

5

−5

x y

O

(6) x−3y−9 = 0

5

−5

5

−5

x y

O

(7) 2y+ 3x=4

5

−5

5

−5

x y

O

(8) 2x+ 3y+ 6 = 0

5

−5

5

−5

x y

O

(9) −x−3y+ 6 = 0

5

−5

5

−5

x y

O

(5)

(1) −x+ 4y−8 = 0

5

−5

5

−5

x y

O

(2) −x−2y=−12

5

−5

5

−5

x y

O

(3) x−2y= 8

5

−5

5

−5

x y

O

(4) −x−2y = 2

5

−5

5

−5

x y

O

(5) −x−2y=−8

5

−5

5

−5

x y

O

(6) 4x−3y+ 15 = 0

5

−5

5

−5

x y

O

(7) 4x+ 3y=9

5

−5

5

−5

x y

O

(8) 3y2x= 15

5

−5

5

−5

x y

O

(9) x+ 2y=−4

5

−5

5

−5

x y

O

(6)

(1) −x+ 4y−8 = 0

5

−5

5

−5

x y

O

(2) −x−2y=−12

5

−5

5

−5

x y

O

(3) x−2y= 8

5

−5

5

−5

x y

O

(4) −x−2y = 2

5

−5

5

−5

x y

O

(5) −x−2y=−8

5

−5

5

−5

x y

O

(6) 4x−3y+ 15 = 0

5

−5

5

−5

x y

O

(7) 4x+ 3y=9

5

−5

5

−5

x y

O

(8) 3y2x= 15

5

−5

5

−5

x y

O

(9) x+ 2y=−4

5

−5

5

−5

x y

O

(7)

(1) 4x3y18 = 0

5

−5

5

−5

x y

O

(2) x+ 2y−12 = 0

5

−5

5

−5

x y

O

(3) 2y3x8 = 0

5

−5

5

−5

x y

O

(4) −2y−3x−10 = 0

5

−5

5

−5

x y

O

(5) −3y+x+ 12 = 0

5

−5

5

−5

x y

O

(6) −2y−x−10 = 0

5

−5

5

−5

x y

O

(7) 3y+x= 3

5

−5

5

−5

x y

O

(8) −4y+ 3x+ 8 = 0

5

−5

5

−5

x y

O

(9) 4y+x8 = 0

5

−5

5

−5

x y

O

(8)

(1) 4x3y18 = 0

5

−5

5

−5

x y

O

(2) x+ 2y−12 = 0

5

−5

5

−5

x y

O

(3) 2y3x8 = 0

5

−5

5

−5

x y

O

(4) −2y−3x−10 = 0

5

−5

5

−5

x y

O

(5) −3y+x+ 12 = 0

5

−5

5

−5

x y

O

(6) −2y−x−10 = 0

5

−5

5

−5

x y

O

(7) 3y+x= 3

5

−5

5

−5

x y

O

(8) −4y+ 3x+ 8 = 0

5

−5

5

−5

x y

O

(9) 4y+x8 = 0

5

−5

5

−5

x y

O

(9)

(1) 2yx=2

5

−5

5

−5

x y

O

(2) −x+ 2y= 12

5

−5

5

−5

x y

O

(3) −3y+ 2x−6 = 0

5

−5

5

−5

x y

O

(4) 3y+x= 6

5

−5

5

−5

x y

O

(5) 2y−x= 4

5

−5

5

−5

x y

O

(6) −x−3y+ 18 = 0

5

−5

5

−5

x y

O

(7) −2y+x+ 6 = 0

5

−5

5

−5

x y

O

(8) 2y+x12 = 0

5

−5

5

−5

x y

O

(9) 3x+ 2y+ 8 = 0

5

−5

5

−5

x y

O

(10)

(1) 2yx=2

5

−5

5

−5

x y

O

(2) −x+ 2y= 12

5

−5

5

−5

x y

O

(3) −3y+ 2x−6 = 0

5

−5

5

−5

x y

O

(4) 3y+x= 6

5

−5

5

−5

x y

O

(5) 2y−x= 4

5

−5

5

−5

x y

O

(6) −x−3y+ 18 = 0

5

−5

5

−5

x y

O

(7) −2y+x+ 6 = 0

5

−5

5

−5

x y

O

(8) 2y+x12 = 0

5

−5

5

−5

x y

O

(9) 3x+ 2y+ 8 = 0

5

−5

5

−5

x y

O

Updating...

参照

Updating...

関連した話題 :